Women's knowledge of maternal danger signs during pregnancy: Findings from a cross-sectional survey in Papua New Guinea. (May 2019) - Vallely, LM; Emori, R; Gouda, H; Phuanukoonnon, S; Homer, CSE; Vallely, AJ
Abstract: Objective: To explore knowledge of pregnancy related danger signs among women attending antenatal clinics in Papua New Guinea. Design: Cross-sectional survey undertaken as part of a wider integrated health and demographic survey. Setting: Three sites in Papua New Guinea: Hiri District (Central Province), Karkar (Madang Province) and Asaro (Eastern Highlands Province). Participants: 482 women aged 15–44 years. Findings: Almost all (95.2%; 459/482) women attended for antenatal care at least once; 68.2% attended four or more times. Among women who attended the antenatal clinic, 53.6% (246/459) reported receiving information about danger signs in pregnancy from a health worker. Of these 60.2% (148/246) could recall at least one danger sign. In addition, 16.4% (35/213) of women who did not receive information from the antenatal clinic reported pregnancy related danger signs. Among the 183 women who reported danger signs, 47.5% (87/183) reported fever; 39.3% (72/183) reported vaginal bleeding and 36.6% (67/183) reported swelling of the face, legs and arms. Women who reported receiving information at the antenatal clinic were significantly more likely know any danger signs, compared with women who did not receive information at the antenatal clinic (OR 7.68 (95%CI: 4.93, 11.96); p = <0.001). Knowledge of danger signs was significantly associated with secondary school education, compared with none or only primary education (OR 3.08 (95% CI: 2.06, 4.61); p = <0.001). Conclusions and implications for practice: Every antenatal clinic visit should be used opportunistically to provide women with information about key danger signs during pregnancy and childbirth. Recognising maternal danger signs, together with the importance of seeking early transfer to the health facility and the importance of attending for a health facility birth are critical to improving outcomes for mothers and babies especially in low income settings such as Papua New Guinea.